REFINING SCHOLARLY ARGUMENTS: THE ROLE OF TOULMIN’S QUALIFIERS AND REBUTTALS IN MASTER’S STUDENTS’ RESEARCH ARTICLES IN SINTA JOURNALS - Frisca Clara Wilar; Swita Wulan Kumaat; Olga Rorintulus (Premise: Journal of English Education and Applied Linguistics, 2026)
Academic writing requires argumentative patterns to make it strongly appeal to readers. One argumentative pattern frequently used by writers is the Toulmin Argument Pattern. Some basic elements of the Toulmin Argument Pattern, such as Claim, Data, and Warrant, are often found in academic writing and articles, but many also neglect additional elements, such as qualifiers and rebuttals, so that the writing is not balanced. This article analyzes how Toulmin's additional elements, such as qualifications and rebuttals, strengthen the structure of an article, making it more complete, balanced, and complete, and thus more widely accepted by readers. Using a descriptive qualitative design, this study analyzed three articles written by Indonesian master's students in the 4-indexed Sinta Journal, using the Toulmin Argument Pattern (TAP) as a diagnostic framework. The results revealed and demonstrated that 100% of the articles analyzed by master's students successfully integrated qualifications and rebuttals. The use of these elements correlated significantly with higher quality argumentation, indicating greater rhetorical precision and dialectical balance. The study concludes that master's students demonstrate a developed awareness of rhetorical precision, utilizing qualifiers to limit overgeneralization and rebuttals to anticipate counter-arguments. These results suggest that Toulmin’s model is an effective diagnostic tool and should be explicitly integrated into academic writing curricula to bridge the gap between undergraduate and master's student writing proficiency.